STRATEGI KOMISI PEMILIHAN UMUM DALAM MENINGKATKAN PARTISIPASI PEMILIH PADA PILKADA BUPATI KABUPATEN BANJARNEGARA TAHUN 2017 - Gafisola Faishal Hanif; Puji - Astuti (Journal of Politic and Government Studies, 2023)
Voter participation is an important aspect of supporting the successful implementation of general elections. Through the level of voter participation in the election, it can show how much the public's interest in the next government is running. The importance of voter participation in holding elections is often not in line with what is happening. Banjarnegara Regency is one of the districts that has a low level of increase in participation, only reaching 0,65% from the previous Pilkada. From these problems, two formulations of the problem were taken regarding how the strategy ot the General Election Commission (KPU) in increasing the participation of community voters in the 2017 General Elections for the District Head of Banjarnegara Regency and why the voter turnout rate in Banjarnegara Regency still tends to be low in the 2017 regional election? The purpose of this research is to analyze the strategy of the General Election Commission (KPU) in increasing the participation of community voters in the 2017 General Elections for the District Head of Banjarnegara Regency and the reasons why the voter turnout rate in Banjarnegara Regency still tends to be low in the 2017 regional elections. This research uses strategy theory from George G. Dess and Alex Miller as well as the theory of the concept of voter turnout. The method used is a qualitative descriptive research method, where data were obtained through interviews, observation, documentation and relevant sources such as journals and theories related to this research. The research was conducted at the Banjarnegara Regency KPU, the informants in this study were two members of the Banjarnegara Regency KPU for the 2012 – 2017 period and the 2018 – 2023 period. Data analysis using interactive data analysis through the stages of data reduction, data presentation and concluding the data. The results of this study indicate that the strategy implemented by the KPU of Banjarnegara Regency is quite good, as evidenced by the use of various methods in socializing and making mascots and jingles. However, in some aspects the implementation is still not optimal, such as the less the not optimal use of women’s organizations based in village/urban village, lack of attention to voters with disabilities and the absence of policies made for voters who migrate. There are two main factors that influence the level of voter turnout in Banjarnegara Regency, (1) high numbers of migrants unable to return home on election day and (2) the low level of education of the people of Banjarnegara Regency. Improvement is needed in optimizing the implementation of the Banjarnegara Regency KPU strategy, so that the target of voter participation can be achieved optimally. There are several recommendation for further research: (1) it is recommended that further research be conducted that focuses on the community’s decision to attend or not attend the polling place and (2) the education factor needs to be further investigated regarding the relationship between education level and community participation level.